2012
DOI: 10.4081/ejh.2012.14
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal course of macrophage-like cell accumulation after experimental embolic stroke depending on treatment with tissue plasminogen activator and its combination with hyperbaric oxygenation

Abstract: Inflammation following ischaemic stroke attracts high priority in current research, particularly using human-like models and long-term observation periods considering translational aspects. The present study aimed on the spatio-temporal course of macrophage-like cell accumulation after experimental thromboembolic stroke and addressed microglial and astroglial reactions in the ischaemic border zone. Further, effects of tissue plasminogen activator (tPA) as currently best treatment for stroke and the potentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 102 publications
1
8
0
Order By: Relevance
“…2A). (Similar double labeling patterns were seen in [58] and [59]). Activated microglia had thicker processes and at least 1 focus of CD68-immunoreactivity that was greater than 2.5 μm in diameter (Fig.…”
Section: Methodssupporting
confidence: 85%
“…2A). (Similar double labeling patterns were seen in [58] and [59]). Activated microglia had thicker processes and at least 1 focus of CD68-immunoreactivity that was greater than 2.5 μm in diameter (Fig.…”
Section: Methodssupporting
confidence: 85%
“…Extending this M2 phase of these macrophages and microglia and delaying their transition into the pro-inflammatory M1 phenotype is a desirable effect. Macrophage invasion typically starts around 24 hours post stroke and increases by 3 to 7 days after stroke; however, recent studies have indicated that the increased level of macrophage accumulation in the brain persists to at least 28 days after stroke 27 . Our data show that hMSC treatment of stroke in T2DM rats significantly induces M2 macrophage polarization as well as increases vascular integrity and axonal/WM remodeling in the ischemic brain.…”
Section: Discussionmentioning
confidence: 99%
“…HUCBC treatment promotes M2 macrophage polarization which may contribute to improved neurological outcome. While it is common knowledge that macrophage invasion starts around 24 hrs after stroke and increases by 3 to 7 days after stroke; recent studies have revealed that the increased level of macrophage accumulation in the brain persists to at least 28 days after stroke 41 , lasting up to 1 year after stroke 42 . The links between M2 polarization and HUCBC induced regulation of neuroinflammation, WM and vascular remodeling leading to beneficial effects are not clear and further studies are warranted.…”
Section: Discussionmentioning
confidence: 99%